Oedipus and the Devil : witchcraft, sexuality, and religion in early modern Europe - Roper, Lyndal (Routledge, 1994)
This bold and imaginative book marks out a different route towards understanding the body, and its relationship to culture and subjectivity. Amongst other subjects, Lyndal Roper deals with the nature of masculinity and feminity.
Keywords: Sex role -- Europe -- History.; Witchcraft -- Europe -- History.; Popular culture -- Europe -- History.; Witchcraft -- history; Gender Identity -- history; Rôle selon le sexe -- Europe -- Histoire.; Sorcellerie -- Europe -- Histoire.; Culture populaire -- Europe -- Histoire.; SOCIAL SCIENCE -- Gender Studies.; Popular culture; Sex role; Witchcraft; Europe; Sexo e sexualidade (sociologia); Historia moderna.; Cultura.; Religiao.; Sexualität; Religion; Hexerei; Deutschland; Hekserij.; Sekseverschillen.; Femmes -- Europe de l'Ouest -- Conditions sociales -- 16e siècle.; Sorcellerie et sexualité -- Europe -- Histoire.; Sexualité -- Aspect religieux -- Christianisme.; Augsbourg (Allemagne) -- Moeurs et coutumes -- 16e siècle.; Allemagne -- Moeurs et coutumes -- 16e siècle.; Sex roles -- History; Witchcraft -- History; History